CONTROL OF THE USE OF PLASTIC WASTE IN SEMARANG CITY - Irfatul Chasanah; Zaenal Arifin; Diah Sulistyani; Muhammad Junaidi (UNTAG Law Review, 2020)
The research objective was to study and analyze the control of plastic waste use in Semarang City and how to control the use of plastic waste in Semarang City. Plastic waste is still a big problem in Indonesia, one of which occurs in the city of Semarang. The problem faced is that every day plastic waste continues to increase, one example in TPA Jatibarang every day Semarang residents can produce household plastic waste of 1,300 tons. This research method uses empirical juridical. This research concludes that the Semarang City Government to address the increasing problem of plastic waste has issued Semarang Mayor Regulation Number 27 of 2019 concerning the control of plastic use. In addition, the Semarang City government issued a mayor's circular regarding the elimination of the use of plastic bags in modern shops such as Alfamart, Alfamidi & Indomaret and to support this, companies also disseminate the regulation to the public. The Mayor's Regulation is ineffective due to the lack of socialization to the public and the lack of awareness of the use of plastic as a grocery bag and lack of supervision by the related institutions due to lack of personnel and no clear sanctions for violating the Mayor's Regulation so that there is no deterrent effect for violators.